Pengaruh Akreditasi Dan Kualitas Pelayanan Terhadap Minat Kuliah Di Universitas Indonesia Timur - Aphar, Rahmadani Mutahli; Lantara, A. Niniek F; Tenrisau, Muhammad Akhsan (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract This research aims to analyze the influence of accreditation and service quality on the interest in studying at the University of Eastern Indonesia. This research is motivated by the importance of these factors in improving accreditation and service quality. The research method used is quantitative with a survey approach. Data collection is conducted through the distribution of questionnaires to all students. Data analysis is performed using multiple linear regression analysis. The results of the study indicate that partially, accreditation and service quality have a positive and significant effect on the interest in studying. This means that the higher the level of accreditation and service quality, the higher the interest in studying among students. In addition, the analysis results also show that simultaneously, both independent variables have a positive and significant effect on the dependent variable, namely the interest in studying. Based on the research results, it can be concluded that accreditation and service quality are very important factors in increasing the interest in studying at the University of Eastern Indonesia. Therefore, the University of Eastern Indonesia needs to pay more attention to these two factors so that the interest in studying can continue to be improved. Keywords: Accreditation, Service Quality, Interest in Studying, University of Eastern Indonesia.